SIRT3 mediates hippocampal synaptic adaptations to intermittent fasting and ameliorates deficits in APP mutant mice - Liu, Yong (Nat Commun, 2019)
Intermittent food deprivation (fasting, IF) improves mood and cognition and protects neurons against excitotoxic degeneration in animal models of epilepsy and Alzheimer’s disease (AD). The mechanisms by which neuronal networks adapt to IF and how such adaptations impact neuropathological processes are unknown. We show that hippocampal neuronal networks adapt to IF by enhancing GABAergic tone, which is associated with reduced anxiety-like behaviors and improved hippocampus-dependent memory. These neuronal network and behavioral adaptations require the mitochondrial protein deacetylase SIRT3 as they are abolished in SIRT3-deficient mice and wild type mice in which SIRT3 is selectively depleted from hippocampal neurons. In the App(NL-G-F) mouse model of AD, IF reduces neuronal network hyperexcitability and ameliorates deficits in hippocampal synaptic plasticity in a SIRT3-dependent manner. These findings demonstrate a role for a mitochondrial protein deacetylase in hippocampal neurons in behavioral and GABAergic synaptic adaptations to IF.